The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1071/bi9670959
|View full text |Cite
|
Sign up to set email alerts
|

Population Data for the Transferrin Variants in the Australian Merino

Abstract: SummaryPopulation data for the transferrin varil;mts in the South Australian and Camden Park strains of the Australian Merino are reported. In all, five variants designated A, B, C, D, and E were distinguished. The relationship between these variants and those reported in previous investigations of the Merino and other breeds has been determined. In two out of the six samples there were significant departures from Hardy-Weinberg expectations. It was observed that closed flocks with small effective population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1972
1972
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Deviations from Hardy-Weinberg equilibrium may be due to a variety of causes (Smith, 1970) and data from specific matings may be more useful to evaluate selective forces. Cooper (1967) observed 5 BB : 7 BD : 12 DD lambs from matings of BD X BD, and we observed the opposite trend, with regard to DD homozygotes, of 4 BB : 7 BD : 2 DD ( Table 5). DD sheep have been rare at Babraham, and they have been deficient every year in all matings in which they have been expected, until 1973 when CD ram 18014 mated to CD ewes produced 1 CC : 8 CD : 6 DD lambs.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Deviations from Hardy-Weinberg equilibrium may be due to a variety of causes (Smith, 1970) and data from specific matings may be more useful to evaluate selective forces. Cooper (1967) observed 5 BB : 7 BD : 12 DD lambs from matings of BD X BD, and we observed the opposite trend, with regard to DD homozygotes, of 4 BB : 7 BD : 2 DD ( Table 5). DD sheep have been rare at Babraham, and they have been deficient every year in all matings in which they have been expected, until 1973 when CD ram 18014 mated to CD ewes produced 1 CC : 8 CD : 6 DD lambs.…”
Section: Discussioncontrasting
confidence: 49%
“…All seven of his homozygous lambs were CC. Cooper (1967) observed an excess of heterozygotes in offspring of two rams, one AC and one AD, which he suggested might be due to inbreeding, although he found that for another AD ram the inbred progeny were in a ratio of 30 heterozygotes to 44 homozygotes. Our data suggest a general advantage of heterozygotes when matings involve heterozygous sires.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This was determined by starch gel electrophoresis in a discontinuous buffer system with Tris-citrate buffer at pH 7-6-7-7 and boric acid-sodium hydroxide electrolyte at pH 7-6-80. The notation of A, B, C, D, E is described by Cooper, Bailey and Mayo (1967). Transferrins now labelled G and M may have been present but undetected.…”
Section: Blood-typing Proceduresmentioning
confidence: 99%
“…However, not all the described variants really exist. For a number of them it was found that they were artefacts which were caused by some form of deterioration of the serum samples (Ashton & Ferguson, 1962; see also Cooper, 1967, andStormont et al, 1968). Besides, several further variants were described which were detected in only a few serum samples and no evidence of their genetic control was published.…”
Section: Introductionmentioning
confidence: 99%